Placeless and barrier-free? Connecting place memories online within an unequal society. (June 2021) - Wieser, Leonie
Digital media have a significant impact on how individuals and groups relate to their own as well as shared memories. Digital and online memorialisation has the potential to connect a greater number of disparate agents across physical place boundaries. Using the case study of an online mapping project recording women's migration experiences, this article finds that digital media are indeed used to challenge established place narratives and contest an exclusionary sense of place. This online memory mapping is intended to connect personal memories of local areas across group and place boundaries. Thematic tagging serves as a tool to connect local memories globally. However, these attempts are situated within an unequal society, where resources, time and digital skills are not equally available to all. Offline power relations and social location are thus found to be constitutive of the making of online memory maps and to hinder democratised memory-making of place.